Toxicity of Brewery Effluents (Burukutu Effluent) to Clarias gariepinus and its Effect on some Target Organs - T.O. Ariyomo; A.M. Akinsorotan; E.N. Nwachukwu (Journal of Applied Sciences and Environmental Management)
A 96-hour bioassay was conducted to determine the toxicity of brewery effluent (Burukutu effluent) to Clarias gariepinus juveniles. The fish were exposed to 4 varying concentrations 154, 231, 308, 385 ml/L and a control, 0ml/L. Physiochemical parameters (pH, temperature and dissolved oxygen) of treated water during the study differed significantly from the control (p<0.05). The values of RBC, PCV, Hg reduced as the concentration increased (p<0.05) while the WBC increased (p<0.05) as the concentration increased and the 96h LC50 of 646ml/L was obtained. Clarias gariepinus juveniles exposed to brewery effluent showed behavioural changes such as erratic swimming, loss of equilibrium, gasping for air, loss of reflex, discolouration, and it led to the death of some fish. The histopathological changes of the gills of fish exposed to brewery effluent for 96 hours at different concentrations showed swollen and shortened lamella, epithelial lifting, lamellar degeneration and loss, swollen lamellae with focal epithelial sloughing. The histology of the liver of the fish exposed to varying concentrations showed pigmented macrophages, vacuolation showing the signs of hepatocyte degeneration, fatty changes and pigmented macrophages. The data obtained from this inveinvestigation showed that brewery effluent caused stress inducing effects on Clarias gariepinus during the exposure period.